Studi Kritis Fatwa DSN NO. 15/ DSN-MUI/ IX/ 2000 Tentang Prinsip Distribusi Hasil Usaha Dalam Lembaga Keuangan Syariah - Karimatul Khasanah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
This article explores Fatwa No. 15/DSN-MUI/IX/2000 concerning the Principles of Revenue Sharing in Sharia Financial Institutions, in which according to this fatwa, these institutions can choose two revenue sharing principles, namely: profit sharing and net revenue sharing. Interestingly, the second point of the first general provision in this fatwa asserts that considering the benefits (al-ashlah), the principle of net revenue sharing should be used in the revenue sharing. The words ‘benefit’ and ‘preferably’ have given a great impact on the principle of the net revenue sharing taken into account by the sharia financial institutions nowadays. It can be noticed that there have not been sharia financial institutions that establish the profit sharing in terms of the revenue sharing principles. By employing a critical study toward the revenue sharing theory concerning sharia principles, this study reveals that the net revenue sharing principle did not represent justice to the transacting parties, whereas the profit sharing one demonstrated better justice. Consequently, the fatwa No. 15/DSN-MUI/IX/2000 needs to be reconstructed by eliminating the second point stipulated in the general provision. Few changes in the second point of this fatwa would show a greater effect on the activities and principles determined by the financial institutions in the future.